Human Resources Management Planning for Increasing Precast Productivity Based on PMBOK at XYZ Company - Novika Candra Fertilia; Raden Yudityo Afri Adji (Yayasan Ahmar Cendekia Indonesia, 2020)
In the era of globalization, it will demand every company to produce good quality products and also quickly in the completion of the product. Xyz Company is a company engaged in manufacturing. The company produces PCI Girder, Spunpile, U-ditch, and Barrier. But production activities there is a mismatch between the plans and the realization that has been made by the company, especially on spunpile products. The purpose of this study is to find out occurrences that affect human resource management planning and to find out how to manage these occurrences. For the method used, the authors used the method of interviewing, observing and distributing questionnaires. The analysis used is the validity test, reliability test, frequency index, severity index, and importance index. The results of this study are that Xyz company has 4 variables that are most influential in human resource management planning.